2017
DOI: 10.1111/eth.12628
|View full text |Cite
|
Sign up to set email alerts
|

Subharmonics increase the auditory impact of female koala rejection calls

Abstract: Although non‐linear phenomena are common in human and non‐human animal vocalisations, their functional relevance remains poorly understood. One theory posits that non‐linear phenomena generate unpredictability in vocalisations, which increases the auditory impact of vocal signals, and makes animals less likely to habituate to call repetition. Female koalas (Phascolarctos cinereus) produce vocal signals when they reject male copulation attempts that contain relatively high levels of non‐linear phenomena, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Alternatively, increased F0 could reflect an attempt to produce a more conspicuous signal to draw attention to the caller, perhaps to encourage male sexual attention. In addition, a higher incidence of nonlinear phenomena in female chirps is likely to increase the auditory impact of these calls [ 48 , 49 ] and recent studies of mammal vocal communication have shown that vocalizations with nonlinear phenomena are particularly evocative and hard to ignore [ 50 52 ]. Accordingly, we suggest that the relatively high F0 and greater incidence of nonlinear phenomena in chirps produced during unsuccessful breeding introductions reflects an attempt by females to grab and maintain the attention of male receivers that may be reluctant to mate.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, increased F0 could reflect an attempt to produce a more conspicuous signal to draw attention to the caller, perhaps to encourage male sexual attention. In addition, a higher incidence of nonlinear phenomena in female chirps is likely to increase the auditory impact of these calls [ 48 , 49 ] and recent studies of mammal vocal communication have shown that vocalizations with nonlinear phenomena are particularly evocative and hard to ignore [ 50 52 ]. Accordingly, we suggest that the relatively high F0 and greater incidence of nonlinear phenomena in chirps produced during unsuccessful breeding introductions reflects an attempt by females to grab and maintain the attention of male receivers that may be reluctant to mate.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates these phenomena might serve adaptive functions (Morton ; Fitch et al., ). For example, vocalizations with nonlinearities may allow listeners to better differentiate between individuals of the same species (Rendall, Notman, & Owren, ) and, in particular, subharmonics may alter the way listeners behave around the communicating individual by indicating size or dominance (Fitch et al., ; Morton, ), or caller arousal levels (Charlton et al., ). Also, calls containing noise or rapid jumps in frequency from tonal sound to noise may be more difficult to habituate to and function to get receivers’ attention (Blumstein & Recapet, ; Townsend & Manser, ).…”
Section: Introductionmentioning
confidence: 99%
“…Noisy screams, cries, and other sounds often contain specific structural characteristics that are particularly evocative to listeners. These nonlinear acoustic phenomena are found in vocalizations from a variety of taxa including terrestrial mammals (Blumstein, Richardson, Cooley, Winternitz, & Daniel, 2008;Charlton, 2015;Charlton, Watchorn, & Whisson, 2017;Rendall et al 2009;Riede, Arcadi, & Owren, 2007;Stoeger, Baotic, Li, & Charlton, 2012;Stoeger, Charlton, Kratochvil, & Fitch, 2011;Tokuda, Riede, Neubauer, Owren, & Herzel, 2002;Wilden, Herzel, Peters, & Tembrock, 1998), marine mammals (Tyson, Nowacek, & Miller, 2007), frogs (Pettitt, Bourne, & Bee, 2012), toadfish (Rice, Land, & Bass, 2011), and birds (Fee, Shraiman, Pesaran, & Mitra, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some work has evaluated the functional relevance of NLP in bioacoustic research, with potential purposes such as preventing habituation, inducing perceptual changes, indicating status, individuality, motivation, and physical health (Wilden et al, 1998;Fitch et al, 2002). Exploring this avenue, studies have shown that NLP may indeed indicate physical condition (Riede et al, 2007), arousal state (Blumstein et al, 2008;Garcia et al, 2014), individuality (Volodina et al, 2006), or drawing increased conspecifics attention (Blumstein and Récapet, 2009;Townsend and Manser, 2011;Reby and Charlton, 2012;Charlton et al, 2017). Nevertheless, the connection between the potential function and the production mechanisms associated with NLP has not been investigated to date.…”
Section: Future Research Directions For Excised Larynx Experimentationmentioning
confidence: 99%